2010
DOI: 10.1021/mp100203a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD4+ T Lymphocyte Lineage Outcomes with Targeted, Nanoparticle-Mediated Cytokine Delivery

Abstract: Within the immune system there is an exquisite ability to discriminate between "self " and "nonself" that is orchestrated by antigen-specific T lymphocytes. Genomic plasticity enables differentiation of naïve CD4+ T lymphocytes into either regulatory cells (Treg) that express the transcription factor Foxp3 and actively prevent auto-immune self destruction, or effector cells (Teff) that attack and destroy their cognate target. An example of such plasticity is our recent discovery that leukemia inhibitory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 24 publications
8
93
0
Order By: Relevance
“…For example, it has been shown that polyclonal Tregs can be expanded using NPs coated with leukemia inhibitory factor [98]. A more antigen-specific approach includes using polymeric or monomeric peptide MHC (pMHC), which may selectively delete T cells expressing the cognate T cell receptor that recognizes the pMHC complex.…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…For example, it has been shown that polyclonal Tregs can be expanded using NPs coated with leukemia inhibitory factor [98]. A more antigen-specific approach includes using polymeric or monomeric peptide MHC (pMHC), which may selectively delete T cells expressing the cognate T cell receptor that recognizes the pMHC complex.…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…46 Other groups later showed that IL-6, known to be associated with inhibition of allo-tolerance, 68 promotes differentiation of TH17 cells in the presence of transforming growth factor-b. 61 When exploring possible interactions between LIF and IL-6, a head-to-head study revealed that LIF and IL-6 function as polar opposites in CD4 þ T cells, 34,69 as illustrated in Figure 3. LIF directly promoted the Treg lineage-specific transcription factor, Foxp3, while simultaneously repressing TH17 lineage-specific genes including the transcription factor RORgt: conversely, IL-6 inhibited expression of Foxp3 and promoted RORgt.…”
Section: Lif In T Cellsmentioning
confidence: 99%
“…LIF directly promoted the Treg lineage-specific transcription factor, Foxp3, while simultaneously repressing TH17 lineage-specific genes including the transcription factor RORgt: conversely, IL-6 inhibited expression of Foxp3 and promoted RORgt. 34,69 Thus a critical LIF/ IL-6 axis in T-cell lineage maturation was first identified, as modelled in Figure 4.…”
Section: Lif In T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This nanoformulation should prove to have substantial application for therapeutics in multiple sclerosis. 161 Diagnostic applications for multiple sclerosis include glyconanoparticles formulated from cross-linked iron oxide nanoparticles modified with sialyl Lewis X, a ligand specific for selectins. Magnetic resonance imaging has shown increased accumulation of these targeted nanoparticles in an experimental autoimmune encephalomyelitis rat model.…”
Section: Applications Of Targeted Delivery In Neurological Disordersmentioning
confidence: 99%